Virtual Classroom with Goformative - Paramita, Paulina Erawati; Effendy, Dudy (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The Fourth Industrial Revolution has profoundly reshaped education, accelerating the integration of technology into traditional classrooms. The COVID-19 pandemic further hastened this transformation, necessitating rapid adaptation to remote and online learning. However, educators faced significant hurdles due to a lack of digital skills and familiarity with online platforms. In Indonesia, the education sector shifted towards digital media and technology, enabling flexible and accessible learning experiences irrespective of physical barriers. This report details a community service initiative by Bimbel Ria Pontianak, focusing on Goformative, a digital learning platform, to equip educators with the essential skills for virtual classrooms. The initiative's objectives included introducing Goformative, fostering its effective use, and encouraging technology integration in teaching. Led by an expert lecturer, the seminar and workshop empowered educators, resulting in increased technological proficiency, improved teaching practices, heightened student engagement, and readiness for the digital era. Addressing initial challenges, this initiative signifies a crucial step towards enhancing the quality and accessibility of education in the digital age